2001
DOI: 10.1021/jo005778h
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Gas-Phase Electrophilic Reactivity of Cyclic N-Alkyl- and N-Acyliminium Ions

Abstract: The intrinsic gas-phase reactivity of cyclic N-alkyl- and N-acyliminium ions toward addition of allyltrimethylsilane (ATMS) has been compared using MS(2) and MS(3) pentaquadrupole mass spectrometric experiments. An order of electrophilic reactivity has been derived and found to agree with orders of overall reactivity in solution. The prototype five-membered ring N-alkyliminium ion 1a and its N-CH(3) analogue 1b, as well as their six-membered ring analogues 1c and 1d, lack N-acyl activation and they are, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 58 publications
1
24
0
2
Order By: Relevance
“…4. The parent ion (PI) of PZQ, at m/z 313, is formed by protonation of one of the amide groups [31]. The PZQ MS 2 spectrum, Fig.…”
Section: Mass Spectral Analysis Of Pzqmentioning
confidence: 99%
“…4. The parent ion (PI) of PZQ, at m/z 313, is formed by protonation of one of the amide groups [31]. The PZQ MS 2 spectrum, Fig.…”
Section: Mass Spectral Analysis Of Pzqmentioning
confidence: 99%
“…In the similar N ‐acyliminium ion spirocyclization, Kibayashi et al. have suggested that the spirocyclization preferentially occurs via the intermediacy of five‐membered ring N ‐acyliminium ions rather than via the six‐membered ring analogue such as II , [11] because the LUMO energy of five‐membered ring N ‐acyliminium ions with exocyclic amide carbonyl groups is lower than that of six‐membered ring analogues [12] . Thus, the less electrophilic reactivity of the six‐membered ring N ‐acyliminium ion II would inhibit the cyclization to 7 d .…”
Section: Methodsmentioning
confidence: 99%
“…In the similar N-acyliminium ion spirocyclization, Kibayashi et al have suggested that the spirocyclization preferentially occurs via the intermediacy of five-membered ring Nacyliminium ions rather than via the six-membered ring analogue such as II, [11] because the LUMO energy of fivemembered ring N-acyliminium ions with exocyclic amide carbonyl groups is lower than that of six-membered ring analogues. [12] Thus, the less electrophilic reactivity of the sixmembered ring N-acyliminium ion II would inhibit the cyclization to 7 d. Therefore, exogeneous H 2 O contaminant reacts with the iminium ion moiety in II, yielding the diketone intermediate III which would be led to the unwanted diketone 8 d and α,βunsaturated ketone 9 d (path b). The factors of the unsuccessful cycloisomerization to 7 d could be related to steric bulkiness of an N-Boc group as well as the aforementioned less electrophilic reactivity of six-membered ring N-acyliminium ion II.…”
mentioning
confidence: 99%
“…Wir stellten die Hypothese auf, dass die Schwierigkeit, diese hochreaktiven Iminiumionen zu bändigen, in (1) ihrer extremen Elektrophilie und (2) der Existenz von zwei sich schnell umwandelnden s-cis/strans-Konformern liegen könnte. [20,21] Angesichts der Fähigkeit von sehr starken und umzäunten IDPi-Katalysatoren, Reaktionen mit flexiblen, energiereichen Kationen zu kontrollieren, folgerten wir, dass solche Organokatalysatoren auch eine Lösung für diese seit langem bestehende Herausforderung bieten könnten. Hier berichten wir über eine hoch enantioselektive Silylium-IDPi-katalysierte Mukaiyama-Mannich-Reaktion, bei der Enolsilane mit in situ erzeugten N-(exo-Acyl)iminiumionen reagieren, um verschiedene nützliche α-substituierte Stickstoff-Heterozyklen zu liefern, darunter Zwischenprodukte für verschiedene Naturstoffe (Abbildung 1).…”
Section: Seit Frühen Berichten In Den 1950er Jahren Werden N-unclassified